Endogenous TRAIL-R4 critically impacts apoptotic and non-apoptotic TRAIL-induced signaling in cancer cells - Rambow, Anna-Christina; Aschenbach, Insa; Hagelund, Sofie; Tawfik, Doaa; Gundlach, Jan-Paul; Weiße, Sebastian; Maass, Nicolai; Trauzold, Anna (Frontiers in Cell and Developmental Biology, 2022)
Binding of TRAIL to its death domain-containing receptors TRAIL-R1 and TRAIL-R2 can induce cell death and/or pro-inflammatory signaling. The importance of TRAIL and TRAIL-R1/R2 in tumor immune surveillance and cancer biology has meanwhile been well documented. In addition, TRAIL has been shown to preferentially kill tumor cells, raising hope for the development of targeted anti-cancer therapies. Apart from death-inducing receptors, TRAIL also binds to TRAIL-R3 and TRAIL-R4. Whereas TRAIL-R3 is lacking an intracellular domain entirely, TRAIL-R4 contains a truncated death domain but still a signaling-competent intracellular part. It is assumed that these receptors have anti-apoptotic, yet still not well understood regulatory functions. To analyze the significance of the endogenous levels of TRAIL-R4 for TRAIL-induced signaling in cancer cells, we stably knocked down this receptor in Colo357 and MDA-MB-231 cells and analyzed the activation of apoptotic and non-apoptotic pathways in response to treatment with TRAIL. We found that TRAIL-R4 affects a plethora of signaling pathways, partly in an opposite way. While knockdown of TRAIL-R4 in Colo357 strongly increased apoptosis and reduced clonogenic survival, it inhibited cell death and improved clonogenic survival of MDA-MB-231 cells after TRAIL treatment. Furthermore, TRAIL-R4 turned out to be an important regulator of the expression of a variety of anti-apoptotic proteins in MDA-MB-231 cells since TRAIL-R4-KD reduced the cellular levels of FLIPs, XIAP and cIAP2 but upregulated the levels of Bcl-xL. By inhibiting Bcl-xL with Navitoclax, we could finally show that this protein mainly accounts for the acquired resistance of MDA-MB-231 TRAIL-R4-KD cells to TRAIL-induced apoptosis. Analyses of non-apoptotic signaling pathways revealed that in both cell lines TRAIL-R4-KD resulted in a constitutively increased activity of AKT and ERK, while it reduced AKT activity after TRAIL treatment. Furthermore, knockdown of TRAIL-R4 potentiated TRAIL-induced activation of ERK and p38 in Colo357, and NF-κB in MDA-MB-231 cells. Importantly, in both cell lines the activity of AKT, ERK, p38 and NFκB after TRAIL treatment was higher in TRAIL-R4-KD cells than in respective control cells. Thus, our data provide evidence for the important regulatory functions of endogenous TRAIL-R4 in cancer cells and improve our understanding of the very complex human TRAIL/TRAIL-R system.